Non-contact optical magnetic field sensor based on metamaterial nanomechanics - Lan, Guoqiang (2023)
We demonstrate a non-contact optical magnetic field sensor that is based on actuation of a metamaterial-microcavity by the magnetic Lorentz force. Magnetic field is transduced to a change of the sensor's reflectivity. The microscale proof-of-concept metamaterial magnetometer can be read from a distance and offers 60 μm spatial, about 10 μs temporal, and sub-microtesla magnetic field resolution.